A study on Hypothetical Mergers for Commercial Banks in the South West States of the USA: An Economies of Scale and X-efficiency Analysis. - Walne, Jonathan C (2015)
Using stochastic frontier analysis techniques, this paper attempts to hypothetically merge banks together from the South West States of America using computed economies of scale and x-efficiencies. The empirical analysis follows two stages, the first computes x-efficiency scores for all 34 banks, followed by a second stage which hypothetically merges five new banks based on their economies of scale.